Gut microbiome and liver diseases - Jun Xu; Ning Chen; Zhou Li; Yulan Liu (Fundamental Research)
Symbiotic microbiota plays a crucial role in the education, development, and maintenance of the host immune system, significantly contributing to overall health. Through the gut-liver axis, the gut microbiota and liver have a bidirectional relationship that is becoming increasingly evident as more research highlights the translocation of the gut microbiota and its metabolites. The focus of this narrative review is to examine and discuss the importance of the gut-liver axis and the enterohepatic barrier in maintaining overall health. Additionally, we emphasize the crucial role of the gut microbiome in liver diseases and explore potential therapeutic strategies for liver diseases by manipulating the microbiota.